It’s Right Behind You!: Sound Object Depth Perception in Modern Horror Film Soundscapes - Nathan Ash-Milby; Timothy Hsu (Journal of the Association for Technology in Music Instruction, 2025)
This presentation explores the use of spatial sound design within modern horror films, illustrating the efficacy of three-dimensional sound placement techniques on audience immersion within periphonic and binaural speaker configurations. Viewers will learn research-based methods and technical considerations to enhance audience immersion and engagement within spatial horror soundscapes, as well as spatial sound practices that can be utilized within different applications.
Keywords: Conference